2015
DOI: 10.4103/0976-7800.153606
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms and its effect on quality of life in urban versus rural women: A cross-sectional study

Abstract: Aim and Objective:To analyze the menopause-related symptoms and its impact on quality of life in post-menopausal women from urban and rural area.Materials and Methods:A cross-sectional 1-year study was carried among women of urban (n = 490) and rural (n = 380) areas, attending the outpatient department in the urban area and a house-to-house survey in rural areas, by interviews with the help of a pretested semi-structured standard questionnaire. For assessment of the menopausal symptoms menopause rating scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 11 publications
(10 reference statements)
4
30
2
3
Order By: Relevance
“…The mean age in years of the postmenopausal women in the current study was 56.49±9.9 which was similar to that reported by Sharma et al, Pathak et al and Chuni et al [19][20][21] However, it was higher than that reported by Nayak et al,but lower than that reported by Christian et al and Madhukumar et al [22][23][24] The mean age at menopause of the participants in our study was 45.64±4.58 yrs which was in agreement with those reported by Bagga et al, Mahajan et al, Sarker et al, Sharma et al and Satpathy. [25][26][27][28][29] However, the mean age scores reported by the current study were lower in comparison to those reported by Sharma S et al,Christian et al, Borker et al and Madhukumar et al 19,23,24,30 The proportion of women who entered menopause prematurely was found to be quite high in current study. The results were in agreement to those reported by Lal and Sharma et al 28,31 The important factors responsible for the diversity in attainment of menopause include regional variation, genetic, environment and nutrition.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The mean age in years of the postmenopausal women in the current study was 56.49±9.9 which was similar to that reported by Sharma et al, Pathak et al and Chuni et al [19][20][21] However, it was higher than that reported by Nayak et al,but lower than that reported by Christian et al and Madhukumar et al [22][23][24] The mean age at menopause of the participants in our study was 45.64±4.58 yrs which was in agreement with those reported by Bagga et al, Mahajan et al, Sarker et al, Sharma et al and Satpathy. [25][26][27][28][29] However, the mean age scores reported by the current study were lower in comparison to those reported by Sharma S et al,Christian et al, Borker et al and Madhukumar et al 19,23,24,30 The proportion of women who entered menopause prematurely was found to be quite high in current study. The results were in agreement to those reported by Lal and Sharma et al 28,31 The important factors responsible for the diversity in attainment of menopause include regional variation, genetic, environment and nutrition.…”
Section: Discussioncontrasting
confidence: 52%
“…[25][26][27][28][29] However, the mean age scores reported by the current study were lower in comparison to those reported by Sharma S et al,Christian et al, Borker et al and Madhukumar et al 19,23,24,30 The proportion of women who entered menopause prematurely was found to be quite high in current study. The results were in agreement to those reported by Lal and Sharma et al 28,31 The important factors responsible for the diversity in attainment of menopause include regional variation, genetic, environment and nutrition. 29 However, the role of recall bias and absence of evidence in determining correct age of participants might have influenced this proportion in a detrimental way despite of investigator's best efforts to find out real age of the participants by correlating it with major events.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A cross sectional study conducted by Sharma S and Mahajan N findings of the study were the high proportion s and the scores of MRS were observed in both rural and urban women. 21 The severity of symptoms was found more distressing for rural women. The quality of life in urban society was average and better in rural women.…”
Section: Discussionmentioning
confidence: 94%
“…In a study in Jammu by Sharma and Mahajan[17] revealed that somatic, psychological, and urogenital symptoms were high in rural women than in urban women. Mohamed et al .…”
Section: Discussionmentioning
confidence: 99%